BAFF blockade attenuates acute graft-versus-host disease directly via the dual regulation of T- and B-cell homeostasis - Jeon, Youngwoo; Lim, Jung-Yeon; Im, Keon-Il; Kim, Nayoun; Cho, Seok-Goo (Frontiers in Immunology, 2022)
Introduction B-cell-activating factor (BAFF) is associated with donor-specific antibodies and chronic graft-versus-host disease (GVHD) after allogeneic hematopoietic stem cell transplantation (allo-HSCT). However, the effects of BAFF on T-cell physiological function have not been fully elucidated in acute GVHD. Methods We examined the effects of belimumab, a monoclonal antibody targeting BAFF, for the treatment of acute GVHD. We examined the effects of T cells and B cells separately when inducing GVHD in mouse model. Results Therapeutic functional manipulation of endogenous BAFF can improve acute GVHD during the early post-transplant period. In this study, BAFF was shown to increase the proportions of CD4+IL-17+, CD4+IL-6+ Th17, and CD4+IFN-γ+ Th1 cells and to reduce the proportion of regulatory T (Treg) cells. Furthermore, the belimumab therapy group showed increased B220+IgD+IgM+ mature B cells but decreased B220+IgD−IgM− memory B cells, B220+Fas+GL-7+ germinal center formation, and B220+IgD−CD138+ plasma cells. These results indicate that BAFF can alleviate acute GVHD by simultaneously regulating T and B cells. Interestingly, the BAFF level was higher in patients with acute GVHD after HSCT compared with patients receiving chemotherapy. Conclusion This study suggests that BAFF blockade might modulate CD4 +T-cell-induced acute GVHD early after allo-HSCT and the possibility of simultaneously controlling chronic GVHD, which may appear later after allo-HSCT.